Beban Kerja dan Kelelahan Kerja dalam Pemberian Obat-Obatan High Alert: Implementasi Prosedur Double Check - Yunita Dwi Anggreini; Nurul Hidayah (Malahayati Nursing Journal, 2022)
ABSTRACT Introduction: The safety of drug administration, especially high alert drugs, is an indicator of patient safety. Several conditions such as workload and work fatigue can cause errors in medication administration.Purpose: This study aims to identify the relationship between workload and work fatigue with the application of double checking in the administration of high alert drugs in the intensive care unit at RSUD dr. Soedarso Pontianak.Method: This study uses an analiytic observational design with a cross-sectional approach. The research sample was 49 intensive nurses at RSUD dr. Soedarso Pontianak who was selected by accidental sampling technique. The instruments used in data collection consisted of a NASA TLX questionnaire to measure workload, a Fatigue Assessment Scale (FAS) questionnaire to measure work fatigue and a nurse implementation questionnaire in the implementation of double checking in the administration of high alert drugs.Result: The results showed that work fatigue was related to the application of double checking in the administration of high alert drugs in the intensive care unit, while workload was not related. Conclusion: There is a correlation between work fatigue and the implementation of double checking in the administration of high alert drugs in the intensive care unit. Keywords : double checking, high alert drug, work fatigue, workload   ABSTRAK Pendahuluan:  Keamanan pemberian obat terutama obat high alert merupakan indikator keselamatan pasien. Beberapa kondisi seperti beban kerja dan kelelahan kerja dapat menyebabkan terjadinya kesalahan dalam pemberian obat-obatan.Tujuan: Penelitian ini bertujuan untuk mengidentifikasi hubungan beban kerja dan kelelahan kerja dengan penerapan double checking dalam pemberian obat high alert di unit perawatan intensif di RSUD dr. Soedarso Pontianak.Metode Penelitian: Penelitian ini menggunakan desain observasional analitik dengan pendekatan crossectional. Sampel penelitian adalah 49 perawat intensif RSUD dr. Soedarso Pontianak yang dipilih secara accidental. Instrumen yang digunakan dalam pengumpulan data terdiri dari kuesioner NASA TLX untuk mengukur beban kerja, kuesioner Fatigue Assessment Scale (FAS) untuk mengukur kelelahan kerja dan kuesioner implementasi perawat dalam pelaksanaan double checking dalam pemberian obat-obatan high alert.Hasil: Hasil penelitian diketahui kelelahan kerja berhubungan dengan penerapan double checking dalam pemberian obat high alert di unit perawatan intensif sedangkan beban kerja tidak berhubungan.Kesimpulan: Ada korelasi antara kelelahan kerja dengan implementasi double checking dalam pemberian obat-obatan high alert di unit perawatan intensif. Kata kunci: Beban kerja, double checking, kelelahan kerja, obat high alert